Approaches for development of functional and low gluten bread from sorghum: A review. Issue 11 (26th September 2022) - Sharanagat, Vijay Singh; Singh, Lochan; Nema, Prabhat K.
Abstract: The demand for low gluten and gluten‐free products in the market has increased remarkably in recent years owing to diseases derived/provoked by the consumption of gluten. Gluten withdrawals from the diet is the main approach to prevent the incidence of celiac symptoms. Attempts are being made to identify different non‐wheat sources of foods with desirable characteristics. Sorghum is one such identified food grain. Diversified products have fetched the limelight, but bread being a widely consumed food product has been researched widely. Despite enormous work carried out on gluten‐free bread, the approaches utilized for bread development from sorghum have not been documented systematically. The present study thus reviews the literature published in the last 10 years to identify the distribution/spread of these studies, the method used for modification of sorghum for bread, the advancements made, the associated challenges, and future prospects. Practical applications: It was observed through published literature that flour and dough modification offered an advantage over unprocessed sorghum flour. In most cases, 20–30% replacement of wheat flour by sorghum seemed feasible for quality bread products while only a few studies could make 100% sorghum‐based bread. Additionally, the additives, ingredients, emulsifiers, enzymes, microbes, etc. addition improved bread properties. However, the number of studies published on every aspect is limited while some approaches are yet to be explored. Hence, the present review will help to identify the work done on sorghum bread and, gap and challenges associated with the development of gluten‐free sorghum bread.